Possibility Theory and the Risk - Georgescu, Irina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book deals with some of the fundamental issues of risk assessment in grid computing environments. The book describes the development of a hybrid probabilistic and possibilistic model for assessing the success of a computing task in a grid environment
Introduction -- Generalities on fuzzy sets -- Possibilistic indicators -- Possibilistic risk aversion -- Expected utility operators and possibilistic risk aversion -- Multidimensional possibilistic risk aversion -- Risk aversion with mixed parameters -- Credibility theory -- Concluding remarks.
Keywords: Engineering; Artificial intelligence; Distribution (Probability theory).; Finance; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Probability Theory and Stochastic Processes; Financial Economics